2018
DOI: 10.1371/journal.pone.0206924
|View full text |Cite
|
Sign up to set email alerts
|

Getting to the root of the matter: Water-soluble and volatile components in thermally-treated biosolids and biochar differentially regulate maize (Zea mays) seedling growth

Abstract: The use of thermally treated biomass, including biochar, as soil amendments can improve soil fertility by providing nutrients, stable C and improving soil water-holding capacity. However, if the degree of carbonization is low, these soil amendments can lower crop productivity as a result of high salinity or organic compounds. The overall effect of these soil amendments is mediated by complex relationships between production conditions, soil properties and environmental conditions. This study aimed to 1) charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Guerena et al [69] found that the removal of VM with an acetone extraction in low-temperature biochar resulted in an increase in plant growth, which was attributed to phytotoxicity effects of the chemical constituents in the VM rather than bioavailable C effects on N availability. There are other examples of chemicals in VM that can have toxic effects on soil microbes [70] and plant growth [71].…”
Section: Discussionmentioning
confidence: 99%
“…Guerena et al [69] found that the removal of VM with an acetone extraction in low-temperature biochar resulted in an increase in plant growth, which was attributed to phytotoxicity effects of the chemical constituents in the VM rather than bioavailable C effects on N availability. There are other examples of chemicals in VM that can have toxic effects on soil microbes [70] and plant growth [71].…”
Section: Discussionmentioning
confidence: 99%
“…A similar trend was noted in another report [2] when the temperature was increased to 750 • C, resulting in the loss of aromatic groups due to the high-temperature. As an organic amendment to improve soil nutrition, the use of the low-temperature (400 • C) biochars having easily-biodegradable carbons would be favorable for plant growth by stimulating soil microorganisms [19,20]. On the other hand, biochars pyrolyzed at 600 • C and enriched with recalcitrant chemical composition would be more suitable not only for carbon sequestration via the use in composting or soil amendment but also for N 2 O reduction during composting [2].…”
Section: Chemical and Physical Characteristics Of Biocharsmentioning
confidence: 99%
“…Moreover, shoot growth was promoted in all treatments, and biochars with greater WSOCs content (350-500 °C) exhibited longer shoots than those obtained at higher temperatures (550-650 °C), suggesting that WSOCs could be involved in the enhancement of plant growth. Backer et al [9] also showed that VOCs and WSOCs from biosolids (270 °C-10 min, 320 °C-20 min) and softwood chips (500 °C, slow pyrolysis) did not affect maize seed germination and shoot and root lengths after a 4-d incubation period, and even a stimulatory effect on shoot length was observed by the VOCs emitted by one of the biosolids (320 °C).…”
Section: Bioassay Of Biochar Water-extractable Substancesmentioning
confidence: 99%
“…The presence of volatile organic compounds (VOCs) and water-soluble organic compounds (WSOCs) in biochars has been associated with both positive and negative biological effects (including plants, microorganisms and aquatic organisms) [9,14,64,69]. For instance, Deenik et al [20] reported reduced germination of radish and corn seeds when subjected to high volatile matter charcoal extracts of macadamia nut shell (430 °C).…”
Section: Bioassay Of Biochar Water-extractable Substancesmentioning
confidence: 99%
See 1 more Smart Citation